HELP PLS
Describe how the graph of y= x2 can be transformed to the graph of the given equation.

y = (x - 13)2 + 6

Shift the graph of y = x2 right 13 units and then up 6 units.
Shift the graph of y = x2 left 13 units and then up 6 units.
Shift the graph of y = x2 up 13 units and then right 6 units.
Shift the graph of y = x2 left 13 units and then down 6 units.

Respuesta :

Answer:

Shift the graph of y = x2 left 13 units and then up 6 units.

Step-by-step explanation:

Answer:

You start with the graph y=x^2, you shift the graph right 13 units to get y=(x-13)^2, then you shift the graph up 6 units to get y=(x-13)^2+6. Hope this helps!